ANALISIS IMPOR BERAS DI INDONESIA (RICE IMPORT DEVELOPMENT ANALYSIS IN INDOENSIA) - HENDRI, AFIF (Perwira Journal of Economics & Business, 2023)
Indonesia is one of the largest rice consuming countries in the world. Rice is a staple food that experiences many problems in providing stock. Domestic rice production has not been able to meet national consumption needs, so the government needs to import rice from abroad. The reason why Indonesia has to import rice is the decreasing area of ​​rice fields. Many rice fields that were originally used for rice farming have been converted to other economic activities. Increasing population growth is a challenge for the government in meeting national rice needs. This research aims: (1) To determine the development of rice imports in Indonesia for the period 2011 to 2020. (2) To determine the contribution of rice imports in Indonesia to the availability of national rice stocks for the period 2011 to 2020. This research uses a case study method with a quantitative approach. The data used is secondary data for the period 2011 to 2020, namely the volume of Indonesian rice imports for the period 2011 to 2020, the value of Indonesian rice imports for the period 2011 to 2020 and the volume of domestic rice production for the period 2011 to 2020. The analysis used is descriptive statistical analysis and contribution analysis. rice imports to national rice stocks. The research results explain that (1) The development of rice imports in Indonesia for the period 2011 to 2020 is fluctuating. Average Indonesian rice imports are 1,138 235.1 tonnes per year. The highest rice imports occurred in 2011 amounting to 2,750,476 tons. (2) The average contribution of Indonesian rice imports to the national rice stock is 2.5 percent, namely 1,138235.1 tons per year. Most of Indonesia's rice imports come from Vietnam and Thailand.